Aid alignment for global health research: the role of HIROs - Viergever Roderik F (Health Research Policy and Systems, 2011)
Abstract The lack of a mechanism that aligns financial flows for global health research towards public health priorities limits the impact of health research on health and health equity. Collaborative groups of health research funders appear to be particularly well situated to ameliorate this situation and to initiate discussion on aid alignment for global health research. One such group is the Heads of International Research Organizations (HIROs), which brings together a large number of major government and philanthropic funders of biomedical research. Surprisingly, there is hardly any information publicly available on HIROs' objectives, or on how it aims to achieve more harmonization in the field of research for health. Greater transparency on HIROs' objectives and on its current efforts towards addressing the gap between global health research needs and investments would be desirable, given the enormous potential benefits of more coordination by this group.